Critical Synthesis Package: Readiness for Interprofessional Learning Scale (RIPLS) - Juliann Binienda (Association of American Medical Colleges, 2015)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Readiness for Interprofessional Learning Scale (RIPLS), and (2) a copy of the RIPLS instrument, developed by Glennys Parsell, Senior Research Associate, and John Bligh, FRCGP. The RIPLS is a 19-item, 5-point Likert scale self-reporting tool that assesses perceptions of healthcare students' knowledge, skills, and attitudes regarding readiness to learn with other healthcare professionals. It is divided into three validated subscales. The Teamwork/Collaboration subscale assesses the valuing of cooperative learning and respecting students from other healthcare professionals, and the Negative Professional Identity subscale measures the tendency of an individual to value and benefit from collaborative relationships with other healthcare professionals. The Roles and Responsibilities subscale measures the practical application of interprofessional skills with other healthcare professional students. Both subscale scores and total scores can be rated. Overall high scores indicate a more positive attitude toward interprofessional learning experiences. It can be used to measure responses to specific interprofessional learning experiences or formatively for planning interprofessional educational activities. It can be administered to a vast array of healthcare professional students at all levels of training either online or in paper/pencil format. Validity and reliability studies have been conducted in efforts to translate the RIPLS into several different languages. Overall RIPLS scores demonstrate appropriate reliability and validity measures but the subscale factor analyses indicate that they need further study to determine suitability of the items. Highest reliability and validity subscales were found with the Teamwork/Collaboration and the Professional Identity subscales with the Roles and Responsibilities subscale demonstrating the least reliable analyses. It is recommended that validity studies continue to finely hone the items in each subscale with perhaps adding additional questions related to patient care benefits of interprofessional practice.